Simultaneous saccharification and fermentation of cellulosic waste for bioethanol production using Saccharomyces cerevisiae ATCC 24859 - Wai Kin., Lee (Universiti Malaysia Sarawak (UNIMAS), 2015)
The utilization of energy has subsequently surged up by 16 fold as human population becomes 4 times larger in the 21st century. Thus, fossil fuels are foreseen to be vastly diminished by 2050. Therefore, to improve the sustainability of energy production, cellulosic office waste materials are proposed to be used as substrates for bioethanol production. This research aims to study the hydrolysis of cellulose to fermentable sugar as well as to analyze the bioethanol production via simultaneous fed-batch saccharification and fermentation performed in the same vessel, using cellulosic office waste as substrate.